Olfactory dysfunction and anosmia awareness in coronavirus disease 2019 pandemic - Juvekar, Meenesh; Sarkar, Baisali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Raise awareness of anosmia association in Coronavirus pandemic. Current finding about Coronavirus infection and its association with olfactory dysfunction and anosmia is reviewed. The exact mechanism of Coronavirus on the Olfactory system is still unresolved. The olfactory dysfunction is due to local inflammation of the nasal cavity or viral-induced olfactory nerve damage or both. Screening of all patients coming with anosmia should be done to early diagnose the disease and isolate and treat accordingly. Olfactory dysfunction is the most common clinical feature of coronavirus disease 2019 with anosmia being the most distinguished sign with patient may present with sudden onset anosmia as single clinical feature or in association with taste dysfunction and / or dry cough, sore throat, pharyngitis, fever. Clinician should be alert of anosmia and diagnose, isolate and treat patients accordingly.